Protective effects of alendronate in Triton X-100-induced hyperlipidemia in rats - Parwin, Ashiyana; Najmi, Abul Kalam; Ismail, Mohd Vasim; Kaundal, Madhu; Akhtar, Mohd (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: The aim of the present study was to evaluate the protective effects of alendronate (used in osteoporosis disease) in Triton X-100 (a polyethylene glycol-based non-ionic surfactant)-induced hyperlipidemia in rats. Materials and Methods: The animals were randomized into seven groups receiving different treatments for 21 days, and alendronate was administered (1.5 and 3 mg/kg body weight, per orally (p.o.) by oral gavage). On day 21, the rats were anesthetized and decapitated, blood samples were extracted, and the livers were dissected for various biochemical tests and histopathological examinations. Results: The biochemical parameters, total cholesterol (TC), triglycerides (TGs), low-density lipoprotein-cholesterol (LDL-C), very low-density lipoprotein-cholesterol (VLDL-C), thiobarbituric acid reactive substances (TBARS), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and atherogenic index, were increased, and reduction in high-density lipoprotein-cholesterol (HDL-C) levels was observed following Triton X-100 treatment to rats. Alendronate (1.5 and 3 mg/kg) produced a dose-dependent reduction in serum TC, VLDL-C, TGs, ratio of TC/HDL-C, ALT, AST, and TBARS. It significantly increased the HDL-C and superoxide dismutase levels but did not cause a significant decrease in serum LDL-C and/or an increase in catalase levels. Histopathological examinations of alendronate showed beneficial effects with lower capsular thickening, slight enlargement of the hepatocytes at the margin, and lower inflammatory cell infiltration. Conclusion: Alendronate showed dose-dependent antihyperlipidemic and hepatoprotective effects. It may serve a dual purpose as anti-osteoporotic and hypolipidemic by reducing blood cholesterol and TG synthesis and offering hepatic protection Cite this article as: Parwin A, Najmi AK, Ismail, MV, Kaundal M, Akhtar M. Protective effects of alendronate in Triton X-100-induced hyperlipidemia in rats. Turk J Gastroenterol 2019; 30(6): 557-64